Controlled synthesis of topological insulator nanoplate arrays on mica. - Li, H; Cao, J; Zheng, W; Chen, Y; Wu, D; Dang, W; Wang, K; Peng, H; Liu, Z (2012)
The orientation- and position-controlled synthesis of single-crystal topological insulator (Bi(2)Se(3) and Bi(2)Te(3)) nanoplate arrays on mica substrates was achieved using van der Waals epitaxy. Individual ultrathin nanoplates with the lateral dimension up to ~0.1 mm or uniform thickness down to 1-2 nm were produced. Single-Dirac-cone surface states of nanoplate aggregates were confirmed by angle-resolved photoemission spectroscopy measurements. The large-grain-size, single-crystal nanoplate arrays grown on mica can act as facile platforms for a combination of spectroscopy and in situ transport measurements, which may open up new avenues for studying exotic physical phenomena, surface chemical reactions, and modification in topological insulators.